Karyogram in neonatology: Necessity or past? - Svjetlana Grubeša Raguž; Marjana Jerković Raguž; Marija Novaković Bošnjak; Darinka Šumanović-Glamuzina; Tomica Božić (Global Medical Genetics)
Objective: This research was conducted at the Clinic for Children's Diseases of the University Clinical Hospital (SKB) Mostar. The aim of this study is to assess the frequency and reasons for performing karyotyping in neonatology practice over the past 15 years in the Herzegovina region. Material and methods: A retrospective epidemiological study was conducted covering a 15-year period from January 1, 2009, to December 31, 2023. The study included 150 newborns who underwent karyotype testing at the Intensive Care and Neonatology Department of the Clinic for Children's Diseases at University Clinical Hospital (SKB) Mostar. Results: Over the 15-year period, 48% (73/150) of the karyotypes were classified as normal, while 51% (77/150) were identified as pathological. The most common chromosomal abnormality was trisomy 21, which accounted for 70.13% (54/77) of the pathological cases. The results indicated that a majority of the fathers were older than 35 years (62.33%, or 48/77), whereas the age of the mothers was not statistically significant in this study. Additionally, 57% of multiparous women gave birth to children with chromosomal abnormalities. Premature newborns were more likely to have positive karyotype results. Conclusion: This research found no significant difference in the occurrence rates of pathological versus physiological karyotypes. Just over 50% of the children had confirmed karyotype deviations from normal variations. However, this suggests that healthcare resources may be misallocated in performing karyotyping, as the significance of the results may not always justify the testing.